Rings and modules characterized by opposites of injectivity - Alizade, Rafail; Buyukasik, Engin; Er, Noyan (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2014)
In a recent paper, Aydogdu and Lopez-Permouth have defined a module M. to be N-subinjective if every homomorphism N -> M extends to some E(N) -> M, where E(N) is the injective hull of N. Clearly, every module is subinjective relative to any injective module. Their work raises the following question: What is the structure of a ring over which every module is injective or subinjective relative only to the smallest possible family of modules, namely injectives? We show, using a dual opposite injectivity condition, that such a ring R is isomorphic to the direct product of a semisimple Artinian ring and an indecomposable ring which is (i) a hereditary Artinian serial ring with J(2) = 0; or (ii) a QF-ring isomorphic to a matrix ring over a local ring. Each case is viable and, conversely, (i) is sufficient for the said property, and a partial converse is proved for a ring satisfying (ii). Using the above mentioned classification, it is also shown that such rings coincide with the fully saturated rings of Trlifaj except, possibly, when von Neumann regularity is assumed. Furthermore, rings and abelian groups which satisfy these opposite injectivity conditions are characterized.
Keywords: Injective; Subinjective; QF ring; Artinian serial; Fully saturated; Mathematics